2021
DOI: 10.1080/08870446.2021.1928668
|View full text |Cite
|
Sign up to set email alerts
|

“We shouldn’t waste a good crisis”: the lived experience of working on the frontline through the first surge (and beyond) of COVID-19 in the UK and Ireland

Abstract: Objective: Frontline workers have shown extraordinary resilience and sustained efforts since the outbreak of COVID-19. The present study used semi-structured interviews with 38 frontline workers in the UK and Ireland to explore the psychological impact of working through COVID-19. Design: The qualitative data were analysed systematically using thematic analysis. Results: Four themes were interpreted: 1)) "I've stopped turning the telly on. I've had to because the news was making me ill": An ecosystem of influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 54 publications
(47 reference statements)
4
40
0
Order By: Relevance
“…Recent research that has sought to understand how frontliners have fared during this time has highlighted the emergence of burnout, anxiety, psychological distress, and even post-traumatic stress symptoms ( De Boni et al, 2020 ; Giorgi et al, 2020 ; Porter et al, 2021 ; Sumner and Kinsella, 2021a ). Whilst different sectors of the frontline have some unique concerns and troubles, they are largely similar in their experiences of trauma, stress, and with their experiences of the impact the pandemic has had on their welfare ( Kinsella et al, 2021 ). While findings have consistently demonstrated the negative psychological consequences of working on the frontline, fewer studies have considered which specific social-psychological factors may be protective or harmful to those working in highly challenging circumstances over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research that has sought to understand how frontliners have fared during this time has highlighted the emergence of burnout, anxiety, psychological distress, and even post-traumatic stress symptoms ( De Boni et al, 2020 ; Giorgi et al, 2020 ; Porter et al, 2021 ; Sumner and Kinsella, 2021a ). Whilst different sectors of the frontline have some unique concerns and troubles, they are largely similar in their experiences of trauma, stress, and with their experiences of the impact the pandemic has had on their welfare ( Kinsella et al, 2021 ). While findings have consistently demonstrated the negative psychological consequences of working on the frontline, fewer studies have considered which specific social-psychological factors may be protective or harmful to those working in highly challenging circumstances over time.…”
Section: Introductionmentioning
confidence: 99%
“…Solidarity appraisal first emerged as a concept as a result of our work on the CV19 Heroes project, 1 which was established to track the welfare of frontline workers of any and all sectors in the UK and Republic of Ireland (RoI) in March 2, 020. 2 The importance of solidarity across all sectors of frontline working first became apparent through qualitative explorations of frontline workers' experiences during the summer of 2020 ( Kinsella et al, 2021 ). Specifically, participants across all sectors (not limited to healthcare) often cited feeling that the government and the public were not working “with” them, most notably through representations in the media of pandemic denial, rule breaking, and inconsistency of messaging ( Kinsella et al, 2021 ; Sumner and Kinsella, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…Some participants felt validated by the public applause that was given at the start of the pandemic. Others were less impressed by this, expressing the view that this public approval would be temporary-these varied responses resonate with previous Irish/UK research [32]. Some nurses stated that being given some tangible recognition for their work by the government and employers in the form of increased pay, shorter working hours and/or increased annual leave would be a more meaningful response to their efforts.…”
Section: Discussionmentioning
confidence: 86%
“…The INMO study suggests that during COVID-19, nurse staff shortages have been very high and that it is critical to investigate the risks posed by the pandemic to nurses [3]. A small body of work comprising qualitative, reflective and observational cohort studies on the experiences of healthcare workers, including nurses, in Ireland, has found that the most challenging aspects of the pandemic have been limited resources and understaffing [3,30], adapting models of care [31] and psychological distress and occupational stress [9,32]. Our research adds to this small but growing body of knowledge by considering how gender or age implications may influence the responses of nurses working through the COVID-19 pandemic in Ireland in the context of these policies and health challenges and the impact on nurses' retirement decisions.…”
Section: Organisational Policies and Health Challenges For Nurses In Ireland During Covid-19mentioning
confidence: 99%
See 1 more Smart Citation